Samotność w prywatnym świecie - Topp, Izolda (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2014)
The text is concentrated on relations between concepts of privacy and solitude nowadays. The author claimed that privacy replaced traditional metaphors and images of solitude like island, mountain or dessert. Protection of privacy and bringing it to the limelight, privatization of religion and the special place occupied in contemporary culture by a search for one’s own identity reveal not only a change in society’s ideas about privacy, but also its axiotic dimension connected with authenticity, creativity and freedom. The meaningful result of this process is connected with replacing religious Transcendence by private individual internal experience, which became unrecognizedand mysterious for the subject itself. It proved to new conceptualization of privacy and ofsolitude as well.